2022
DOI: 10.1002/hpm.3422
|View full text |Cite
|
Sign up to set email alerts
|

Profile and determinants of intention to migrate by early career doctors in Nigeria: A report from CHARTING study

Abstract: Introduction Recently, there has been an upsurge in the migration of medical personnel, especially early career doctors (ECDs) from low‐ and middle‐income countries, Nigeria inclusive, to high‐income countries with wide‐ranging consequences on the social and economic systems of the donor countries. This study assessed the profile and determinants of intention to emigrate by ECDs in Nigeria. Methods A cross‐sectional study conducted among Nigerian ECDs from nine tertiary hospitals. Socio‐demographic characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
1
8
0
1
Order By: Relevance
“…HCWs who perceived that the pandemic did not affect their interpersonal relationships and who were neutral towards the governmental response had lower odds of increased migration intent after the pandemic. These findings relate to those of a study by Adeniyi et al [ 36 ] before the pandemic, which reported that political factors had a low influence (5.5%) on Nigerian HCWs. Instead, they reported that family ties and the desire to serve the nation were the main motives to stay in their home countries.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…HCWs who perceived that the pandemic did not affect their interpersonal relationships and who were neutral towards the governmental response had lower odds of increased migration intent after the pandemic. These findings relate to those of a study by Adeniyi et al [ 36 ] before the pandemic, which reported that political factors had a low influence (5.5%) on Nigerian HCWs. Instead, they reported that family ties and the desire to serve the nation were the main motives to stay in their home countries.…”
Section: Discussionsupporting
confidence: 88%
“…Physicians were generally more likely to report intention to migrate than nurses and other professionals. A recent migrant profiling study by Adeniyi et al [ 36 ] reported that early-career physicians migrate to seek better postgraduate training and higher salaries. In general, healthcare professionals from developing countries migrate to countries with robust health systems and more opportunities for advancement [ 22 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to test the presented research hypotheses, we applied a binary logit model, both as a result of the type of data analyzed, and as a result of the fact that the literature in this field predominantly uses this type of questionnaire analysis. Similar studies [ 29 , 31 , 66 , 67 , 68 , 69 ] that analyzed the determinants of the migration intention of medical university students or medical staff used logistic regression in their econometric analysis; thus, for the binary dependent variable, it is the most suitable method of econometric analysis [ 70 ].…”
Section: Methodsmentioning
confidence: 99%
“…The unanimous opinion of the specialists is that the motivation for mobility is provided by the clearly increasingly attractive opportunities for a professional career. If specialization internships target professional subfields and an education level/profile of interest to the host country, the professional career continues, most of the time through occupation in the host country [ 15 , 28 , 29 , 30 , 31 ]. In addition, for less developed countries, the motivation of substantially better remuneration than in the country of origin makes the investment in education for the health sector open to being capitalized on in a different market to the location of professional education/training.…”
Section: Introductionmentioning
confidence: 99%